2018
DOI: 10.1111/wvn.12286
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Emergency Room Visits and In‐Hospitalizations by Implementing Best Practice for Transitional Care Using Innovative Technology and Big Data

Abstract: Using health information exchange to deliver appropriate and timely evidence-based clinical decision support in the form of care transition alerts and assessment of social determinants of health, in conjunction with data science methods, demonstrates the value of nursing care and resulted in achieving the Quadruple Aim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 17 publications
0
35
0
6
Order By: Relevance
“…Thus, WIA is a useful model to consider in tandem with the grounded theory of relationship‐based care when developing technology‐aided approaches to personalize care and support clinical decision‐making in the homecare setting. The use of information technology would enhance communication and support the homecare RNs ability to be informed of changes (Hewner et al., 2018) as they engage all stakeholders and manoeuvre through various barriers when transitioning their patients to supportive care services. Moreover, establishing interoperability standards and shared care planning (Sullivan et al., 2017), supported by nursing informatics, is an effective approach for enriching cross‐sector communication of social needs from within the home, promotes health equity (Matheny et al., 2020), and may help promote a trusting relationship with primary care providers (Lanham et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, WIA is a useful model to consider in tandem with the grounded theory of relationship‐based care when developing technology‐aided approaches to personalize care and support clinical decision‐making in the homecare setting. The use of information technology would enhance communication and support the homecare RNs ability to be informed of changes (Hewner et al., 2018) as they engage all stakeholders and manoeuvre through various barriers when transitioning their patients to supportive care services. Moreover, establishing interoperability standards and shared care planning (Sullivan et al., 2017), supported by nursing informatics, is an effective approach for enriching cross‐sector communication of social needs from within the home, promotes health equity (Matheny et al., 2020), and may help promote a trusting relationship with primary care providers (Lanham et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Delivery of health care in an interrupted, fragmented, or uncoordinated manner contributes to increased healthcare costs and inappropriate healthcare use [66]. Improving continuity of care in this context requires careful coordination across the healthcare continuum [67]. Successful communication between EDs and primary care providers in acute and community settings is an essential component of such interventions and programs [67].…”
Section: Discussionmentioning
confidence: 99%
“…Improving continuity of care in this context requires careful coordination across the healthcare continuum [67]. Successful communication between EDs and primary care providers in acute and community settings is an essential component of such interventions and programs [67]. A recent systematic review that evaluated the effectiveness of several types of interventions and programs (such as care plans, case management, printout case notes, diversion strategies, and social work practitioners) targeting adult frequent ED users, showed that some interventions are effective in reducing visit frequency and improving patient outcomes [68].…”
Section: Discussionmentioning
confidence: 99%
“…Integration with the existing system facilitates health information exchange, which involves reducing unnecessary hospitalizations and emergency visits (Hewner et al. ). Hence, this integration should be addressed promptly because it will be beneficial to policy‐makers and on‐site nurses.…”
Section: Discussionmentioning
confidence: 99%